ACCESSORY NATIVE METALS AND ALLOYS IN IMPACT MELT ROCKS OF THE EL’GYGYTGYN CRATER, CHUKOTKA - Gurov, Е. P.; Permiakov, V.V. (Reports of the National Academy of Sciences of Ukraine, 2024)
An electron microscopic study of impact melt rocks from the south and southeast regions of the El’gygytgyn impact crater revealed the presence of accessory mineralization composed of native metals and alloys. These minerals include alloys of silver, copper, tin, lead, and occasionally, their respective metals. The host impact melt rocks exhibit a vesicular structure and contain numerous fragments of C-rich clayey matter, which are situated within gas vesicles in a glassy matrix. The inner surface of this clayey matter inside gas vesicles serves as the primary substrate for the crystallization of native metals and alloys. The presumed source of these metals is an ore deposit located in the impact melting area of the target during a meteorite impact, while clayey fragments from the bottom sediments of a local lake at the target surface are considered a probable source.